Parental phubbing and smartphone addiction among adolescents - Afrida Mulyaningrum; Fitri Ayu Kusumaningrum (Institut Agama Islam Negeri Langsa, 2022)
This study investigated the correlation between parental phubbing and smartphone addiction among adolescents. The number of participants in this study was 292 adolescents that, consist 76 boys and 216 girls who lived on Java Island with an age range of 12 to 21 years old. This study used the quantitative method with the Likert scale. The measurement for the variables in this study used Smartphone Addiction Scale Short-Version (SAS-SV) by Kwon et al. (2013) and Parental Phubbing by Roberts and David (2016). The analysis result of this study showed a positive correlation between parental phubbing and smartphone addiction among adolescents, with the coefficient of correlation r=0,200 and p<0,001. This finding meant that a higher parental phubbing score would indicate a higher smartphone addiction score. Based on the result, we can conclude that the hypothesis of this study is accepted.